Natural and Enhanced Remediation Systems - Suthersan, Suthan S. (CRC Press, 2009)
Building on the success of bioremediation and phytoremediation technologies, Natural and Enhanced Remediation Systems explores remediation techniques that use the beneficial effects provided by Mother Nature.